The 12th Conference of the International Sports Engineering Association 2018
DOI: 10.3390/proceedings2060213
|View full text |Cite
|
Sign up to set email alerts
|

On the Exposure of Hands to Vibration in Road Cycling: An Assessment of the Effect of Gloves and Handlebar Tape

Abstract: The objective of this work was to assess the effectiveness of cycling gloves and handlebar tape in reducing the vibration transmitted to the cyclist's hands in the classic "hoods" position for shock-type excitation at the front wheel on a bicycle treadmill. Three pairs of conditions were tested on a single participant: (1) With gloves vs. no gloves, no bar tape; (2) With bar tape vs. no bar tape, no gloves; (3) With gloves and bar tape vs. no gloves and no bar tape. We have shown that a rider can expect a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Further tests with different positions on the handlebar and especially with 'top' one, where padded zones completely cover the contact area, could show an effect. Even Drouet et al [5], who used 'hoods' position for the test and gloves from a different brand, found that padded gloves had no significant effect and stated that 'top' position could better match padding layout with the cyclist grip on the handlebar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further tests with different positions on the handlebar and especially with 'top' one, where padded zones completely cover the contact area, could show an effect. Even Drouet et al [5], who used 'hoods' position for the test and gloves from a different brand, found that padded gloves had no significant effect and stated that 'top' position could better match padding layout with the cyclist grip on the handlebar.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations related to the effect of working gloves on hand-arm vibrations transmission have been reported in the literature [4], but few studies go deep into the analysis of the effect of different cycling gloves on vibrations transmission to the hand-arm system. Drouet et al [5] studied the effect of cycling gloves and bar tape on vibrations transmission with only one type of gloves and one subject. This study showed a significant effect of bar tape in reducing the transmitted power and energy through the handlebar, but no significant effect of gloves.…”
Section: Introductionmentioning
confidence: 99%
“…Just few studies explore the effect of cycling gloves on vibrations transmission to the hand-arm system. Drouet et al [1] studied the effect of cycling gloves and bar tape on vibrations transmission, this study showed a significant effect of bar tape in reducing the transmitted power and energy through the handlebar, but no significant effect of gloves.…”
Section: Introductionmentioning
confidence: 92%
“…(3) vibration transmissibility of bicycles, bicycle components, and cycling apparel [14][15][16][17][18][19]; (4) assessments of road surfaces [20][21][22][23][24]; (5) cyclists' sensory perception [2,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rigorous test protocols must be implemented when taking measurements of the vibration transmitted to a cyclist [9]. Typically, four quantities have been used: acceleration [1-3, 7-10, 12-17, 20-24, 27], force [1,9,10,17,19], power [1,3,10,11,17,18,27], and energy [18,25,26]. These quantities are measured at or as close as possible to the cyclist's hands or buttocks to relate to what is experienced by the cyclist.…”
Section: Introductionmentioning
confidence: 99%